Analisis Tingkat Kemandirian keuangan Daerah Pasca Pemekaran Wilayah - Tedi - Rustendi (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2021)
This study aims to determine whether there is a difference in the level of financial autonomous between Kabupaten Tasikmalaya as the origin/parent region is divided and Kota Tasikmalaya that formed as an autonomy region. The study used a case approach in longitudinal data of the budget realization from 2007 to 2018 which is divided into two samples of each 12-fiscal years. Based on the analysis result, Kabupaten Tasikmalaya and Kota Tasikmalaya have low level of financial autonomous, and the pattern of their relationship with the central government in the instructive category. However, based on the hypothesis test results, the financial autonomous level of the two regions is significantly different, where the level of financial autonomous of Kota Tasikmalaya is higher than the level of financial autonomous of Kabupaten Tasikmalaya. In this case, Kota Tasikmalaya has a better chance to utilize regional eoutomy to accelerate regional development and improve the quality of its public services based on local original revenue.Key words: autonomous, fiscal decentralization, local government